The “5 Ws and 1 H” of Sharenting: Findings from a Systematized Review - Cino, Davide (Italian Sociological Review, 2021)
This paper is based on the results of a systematized review analyzing a corpus of empirical literature on the topic of sharenting following the conceptual framework of the 5Ws and 1 H, here mobilized to map the characteristics and modalities of this practice through the analysis of 49 empirical studies. Findings provide information in terms of who shares contents about parenting and children online, what is shared and where (in terms of platforms used), when, as in life phases during which sharenting takes place, why, as in the rationale behind it, and finally how, in terms of parents’ decision-making, governance and privacy strategies about whether and how to share of their parenting and children online. Future directions are finally discussed.